Comparative Study of Inhaled Corticosteroids and Leukotriene Receptor Antagonists in the Management of Paediatric Asthma - Khurram Nawaz, Rizwan Mahmood, Imran Yasin, Husnul Hayat, Sanwal Sardar Nawaz, Muhammad Usman Rafique, (Pakistan Journal of Medical & Health Sciences, 2024)
Background: Asthma is one of the most prevalent chronic respiratory diseases in children, characterized by airway inflammation, hyper-responsiveness, and reversible airflow obstruction. Objective: To compare the clinical effectiveness of inhaled corticosteroids and leukotriene receptor antagonists in improving pulmonary function, symptom control, and reducing exacerbations among children with asthma. Methodology: This comparative prospective observational study was conducted at Department of Pediatric Medicine, Shahida Islam Medical & Dental College, Lodhran from 1st April 2023 to 30th September 2023. A total of 185 children aged 5–15 years with mild to moderate persistent asthma were enrolled and divided into two groups: Group A (n=92) received inhaled corticosteroids (Budesonide or Fluticasone), and Group B (n=93) received an oral leukotriene receptor antagonist (Montelukast). Clinical improvement was assessed over 12 weeks using pulmonary function tests (FEV1, PEFR), symptom frequency, Asthma Control Test (ACT) scores, and exacerbation rates. Results: Both groups showed significant improvement in lung function and symptom control over the study period. However, the inhaled corticosteroids group demonstrated greater improvement in mean FEV1 (from 74.5±8.9 to 87.8±7.6) compared to the leukotriene receptor antagonists group (from 75.2±9.3 to 82.1±8.2; p=0.001). Similarly, astham control test scores improved more significantly in the inhaled corticosteroids group (23.4±2.8 vs. 21.6±3.1; p=0.002). The frequency of exacerbations was lower in the inhaled corticosteroids group (0.6±0.4) than in the leukotriene receptor antagonists group (1.2±0.6; p = 0.001). Both treatments were well-tolerated with only mild and transient adverse effects. Conclusion: Both inhaled corticosteroids and leukotriene receptor antagonists are effective in the management of pediatric asthma; however, Inhaled corticosteroids provide superior control of airway inflammation, symptom frequency, and exacerbation reduction. Keywords: Inhaled corticosteroids, Leukotriene receptor antagonists, Paediatric asthma